LEGAL STATUS OF FARMER ENTERPRISES AND THE PROCEDURE FOR THEIR STATE REGISTRATION - Normurodov Bakhtiyor Zokirovich (Web of Journals Publishing, 2025)
This article explores the legal status of farmer enterprises and the procedure for their state registration under the legislation of the Republic of Uzbekistan. It analyzes the requirements for founding documents, the legal process of registration, and the implications of acquiring legal entity status. The article also addresses practical challenges and offers recommendations for improving legal regulation in the agricultural sector.
Keywords: Farmer enterprise, legal status, agricultural entities, land relations, private property, land rights, entrepreneurship, registration, regulatory and legal framework, legislative improvement, practical experience, economic activity.